Reconstruction of the Norms on the Authority to Stop and Inspect Vessels by Polairud for Alleged Fisheries Crimes in Indonesia's Exclusive Economic Zone - Moch Abdan Salam; Effendy Lod Simanjutak (Jurnal Sosial Teknologi, 2026)
This study aims to analyze the problematic norms of Polairud's authority in stopping and inspecting vessels for suspected fisheries crimes in the Indonesian Exclusive Economic Zone, identify forms of disharmony in regulations between maritime law enforcement officers, and formulate a norm reconstruction model based on legal certainty and harmonization with international maritime law. The research method used was normative juridical with a statutory and conceptual approach, through a review of the 1982 United Nations Convention on the Law of the Sea, the Law on Police, Fisheries, the Indonesian Exclusive Economic Zone, Maritime Affairs, and the Criminal Procedure Code. The results of the study indicate that Polairud's authority in stopping and inspecting vessels in the EEZ still faces unclear norms, conflicting authorities, and procedural gaps, particularly related to first action authority, the legality of ship inspections as special searches, the time limit for termination, and the mechanism for handing over cases between institutions. Horizontal disharmony between Polairud, PPNS KKP, TNI AL, and Bakamla, as well as vertical disharmony between KUHAP, Fisheries Law, Maritime Affairs Law, and Article 73 UNCLOS 1982, has implications for weak legal certainty, potential abuse of power, and the risk of international disputes. The novelty of this research lies in the proposed reconstruction of norms based on first action authority that places Polairud as the initial action authority, the establishment of special maritime search procedures, and the development of a lex specialis maritime criminal procedure model within the framework of integrated maritime law enforcement.